A Perspective on Ottoman Historicity Between Truth and Misconception - maouche, abdelhamid (El Omda in Linguistics and Discourse Analysis, 2022)
History is considered an essential component in the structure and hierarchy of the existence and development of peoples, and one of its fundamental pillars. However, organizing the historical field with absolute precision and within a unified intellectual and consensual framework regarding historical events is nearly impossible. This is confirmed by numerous writings, theses, and diverse theories proposed by historians and researchers in this field. This issue is particularly evident in the history of the Ottoman Empire, which is documented in school curricula and textbooks across various educational levels, from primary to university. These sources, depending on their perspectives, refer to it using different terms such as: Turkish occupation, Turkish mandate, Turkish colonialism, or Turkish invasion. Such representations, whether positive or negative, vary according to the individual’s identity, culture, and ultimate perspective, and they shape the complex relationship between history and memory—especially within the intertwined relations between Islamic–Turkish, Arab–Turkish, and particularly Algerian–Turkish contexts. This raises important questions about the impact of these historical narratives on Algerian youth, both now and in the future: will they be able to critically transcend potential distortions, if they exist, or will